FEM/BEM Techniques for Modelling of Local Fields in Contact Mechanics - Zmindak, Milan; Radziszewski, Leszek; Pelagic, Zoran; Falat, Milos (Communications - Scientific letters of the University of Zilina, 2015)
This contribution contains description of modelling technique of contact problems of bodies with curved surfaces when assumption of infinitesimal displacements can be considered to give sufficient accuracy for both displacement and stress analysis. This assumption considers that the local configuration of the bodies in contact will not be influenced during the deformation process and only dimensions and shape of the contact surfaces and contact pressures will change by the load conditions. Such assumptions enable to reduce the contact problem considerably, if the local contact displacement and stress fields are modelled as local fields inside large elements (sub-domains) using superposition of a local Hertz type field and a smooth field modelled in a classical way using large FEM or BEM technique. A technique of obtaining the complex solution of the bodies in contact as a combination of the local contact field defined by the Boussinesq’s solution and the smooth field modelled by multi-domain BEM is described and considered to be a basis for the modelling and design of contact problems containing large gradient displacements.